La publicidad emitida a través de canal Uno y su impacto social en los usuarios del servicio de TV cable de la ciudad de Cariamanga, en el período de septiembre a diciembre del 2013. Lineamientos alternativos - Loaiza Lima, Eduardo Vicente (2014)
Social communication is a crucial process in the life of human beings, allowing them to interact directly or indirectly with their peers and express their opinions about different aspects that are part of social living, so must be exercised a responsible and loyal to those who are influenced by it. In social media, one of the elements that has broad implications is the publicity, which in one form or another is the financial support for the action of the media. Hence the desire to attract as much publicity as possible, make the media act irresponsibly towards the people who run the above messages. Past conduct gives rise to its disclosure by the media, known as misleading advertising, ie one that uses a series of mechanisms to guide and capture the public's preference for a product, good or service, leading to cheating on their qualities and features to consumers. Misleading advertising, unfortunately is also present in the Ecuadorian media, which is why we have chosen as a reference for this study to Channel One, trying to analyze objectively the publicity that is issued by this means, for course catalog if it is misleading and may generate negative effects on society, and directly on the users and consumers who are influenced by this type of advertising. The paper concludes how could it be otherwise with the approach of a proposal aimed at ensuring that advertising that is broadcast through the media meets the criteria of objectivity, and loyalty to the users and consumers so as not to constitute a form that can generate negative consequences to the detriment of the people involved in the communication process, but rather can fulfill the leading role of the media in the social life.